Incorporating Students’ Funds Of Knowledge To Develop A Sustained Interest In Science - Rohandi, Rohandi (2010)

(untitled)
The objectives of this study were to identify students’ funds of knowledge and learning difficulties they faced in understanding science concepts, to design identified science lessons incorporating students’ funds of knowledge, and to investigate the change in students’ attitudes and interests engaging in science. The connection among students’ culture, home experiences and experiential knowledge of students which is identified as funds of knowledge have been incorporated into the teaching and learning of science that put emphasis on instructional congruence. The study involved two sub-urban Junior High Schools in Indonesia. Two teachers and 173 students (94 males and 79 females) participated in this study.